2017
DOI: 10.1093/jnci/djx058
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study to Identify Susceptibility Loci That Modify Radiation-Related Risk for Breast Cancer After Childhood Cancer

Abstract: Our study provides strong evidence that germline genetics outside high-risk syndromes could modify the effect of radiation exposure on breast cancer risk after childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 37 publications
1
45
0
1
Order By: Relevance
“…For the current report, 96 survivors were selected from the pool of ALL survivors with an available DNA sample using “extreme phenotype” sampling: 48 obese (BMI ≥ 30.0 kg/m 2 ) and 48 normal weight (18.5 ≤ BMI ≤24.9 kg/m 2 ) based on the CCSS 2007 Follow‐up survey. Specifically, eligible participants included adult (age ≥20 years at 2007 survey) survivors of ALL (with no history of bone marrow transplant, recurrence, or subsequent malignant neoplasms), genotyped as part of the CCSS and National Cancer Institute collaborative genome‐wide association study and genetically defined as being predominantly of European ancestry (ie, ≥80%) with details on therapeutic exposures . To form the obese group, we randomly selected 24 obese survivors who had CRT doses of ≥18 Gy and 24 obese survivors who did not receive CRT (ie, chemotherapy only), in order to be able to evaluate the methylation‐association differences by CRT status, one of the strongest risk factors for obesity among adult survivors of pediatric ALL .…”
Section: Methodsmentioning
confidence: 99%
“…For the current report, 96 survivors were selected from the pool of ALL survivors with an available DNA sample using “extreme phenotype” sampling: 48 obese (BMI ≥ 30.0 kg/m 2 ) and 48 normal weight (18.5 ≤ BMI ≤24.9 kg/m 2 ) based on the CCSS 2007 Follow‐up survey. Specifically, eligible participants included adult (age ≥20 years at 2007 survey) survivors of ALL (with no history of bone marrow transplant, recurrence, or subsequent malignant neoplasms), genotyped as part of the CCSS and National Cancer Institute collaborative genome‐wide association study and genetically defined as being predominantly of European ancestry (ie, ≥80%) with details on therapeutic exposures . To form the obese group, we randomly selected 24 obese survivors who had CRT doses of ≥18 Gy and 24 obese survivors who did not receive CRT (ie, chemotherapy only), in order to be able to evaluate the methylation‐association differences by CRT status, one of the strongest risk factors for obesity among adult survivors of pediatric ALL .…”
Section: Methodsmentioning
confidence: 99%
“…Among childhood cancer survivors, approximately 30% of patients receiving ≥10 Gy chest RT develop breast cancer by 50 years . In a genome‐wide association study to identify loci of genetic susceptibility to breast cancer development after RT, the interaction of certain germline variants with ionizing radiation conferred a higher risk of RT‐associated breast cancer in some patients . In another study using GWAS, a genetic locus at 6q21 was associated with higher risk for RT‐associated SMNs in patients treated as adolescents .…”
Section: Survivorship and Long‐term Treatment Sequelaementioning
confidence: 99%
“…Indeed, the data from Morton et al (7) cast an element of uncertainty upon two previously reported associations detected in this setting, at 6q21 and 10q26.13 (8,9). While genetic epidemiological studies of sporadic cancer predisposition in the general population have identified and robustly validated hundreds of variants that influence the risk of most common types of the disease (10), these successes have depended on global collaborative efforts to pool vast numbers of samples for analysis (11–13).…”
mentioning
confidence: 87%